The application of multilateration technology in air traffic control - Li, He Ping (Radiotekhnika, 2017)
In view of the problem that the existing Air Traffic Control (ATC) system is unable to monitor aircrafts which are taking off, landing or moving in the airport. On the basis of the analyzing mission requirements of ATC and the advantage of the multilateration, this paper introduces the multilateration into the ATC application. And the key problems, such as station layout mode, multipath suppression and time difference extraction, are intensively studied. Several tests have been implemented in an airport, and the results illustrate that the proposed method is effective and reliable.